Sumbangsih Kajian Hadis dalam Merespon Radikalisme Agama di Indonesia: Analisis Terhadap Website Onedayonehadith.net - Via Nurhayati (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
One Day One Hadith was born from the rapid development of information technology in the contemporary era, thus forming technological determinism which is characterized by digital piety in several levels of society. This article explains the effectiveness of the hadith learning process in the contemporary era through the One Day One Hadith activity with a short, concise, clear reading model and comprehensive contextual understanding. With contemporary contextual reading, it makes it easier for readers to understand the meaning of the hadith without providing a superior understanding. Apart from that, this activity has a positive impact on religious radicalism that occurs in Indonesia because it provides a down-to-earth understanding. Research data was collected through a research library and interviews with administrators of the onedayonehadith.net website. The findings of this research show that this activity is a form of contribution to the study of hadith in the digital realm which has a big influence on its understanding. Socially, this finding has implications for character formation, in one day one hadith provides its own color for the study of hadith in Indonesia. By distributing hadiths one day at a time, the purpose is to make it easier to find and understand hadith.